The praise of cachaça: the medical-naval discourse on the benefits of sugar cane brandy consumption on board Brazilian Navy ships in the 19th century - Oliveira Filho, Sergio Willian de Castro; Messias, Luana Costa Pierre de (Revista Ingesta, 2020)
In the second half of the 19th century, some physicians from the Brazilian Navy Health Corps wrote reports about the trips they had taken on Brazilian Navy ships. In addition to presenting the description of the nosological aspects of the crews during their voyages, the surgeons of the Navy exposed their medical convictions regarding the ideal way of maintaining the health of the military facing various adversities imposed on seafarers when traveling. Such situation highlighted the importance of medical knowledge in the institution and legitimized it, turning doctors into more than professionals who were devoted to healing, as they would also have in their repertoire the control of the bodies of Navy personnel with ways to maximize their performance on board. Among various aspects regarding practices and behaviors that would enable physical and moral health for the crew, was the consumption of alcoholic beverages by sailors, especially sugar cane brandy. It was argued that the moderate consumption of cachaça by seafarers facing the exhaustive work to which they were exposed would be healthy, inasmuch as its composition was stimulating and refreshing, in addition to being necessary for the organism in colder climates. Nevertheless, such a compliment to cachaça was not an ode to pleasure or sociability, but rather a speech that gave the doctor control over such consumption, which would prescribe the amount and the moment when the “spirit drink” should be used. Having the approaches to the standardization of the bodies and the rise of medical knowledge as a theoretical motto, this article will discuss the focus given by surgeons of the Brazilian Navy to the consumption of brandy by the Navy military in the 19th century.